Senegal : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report, 2007)
This paper focuses on Senegal's second poverty reduction strategy paper (PRSP-II). It summarizes the results of the participatory PRSP review process prior to final validation and adoption by the government. As an economic and social policy document for growth and poverty reduction that draws legitimacy from an underlying participatory process, it sets poverty reduction targets for the medium and long terms, defines progress indicators, and establishes annual and intermediate targets. It also identifies the resources to be mobilized to achieve the desired results.